Penentuan Status Mutu Air dan Status Trofik di Perairan Danau Maninjau : Determination of Water Quality Status and Trophic Classification of Lake Maninjau - Astried Sunaryani (Jurnal Teknologi Lingkungan, 2023)
Lake Maninjau has been establihed as one of the National Priority Lakes that is used for hydroelectric powerplant, tourism, fisheries and aquaculture. The rapid increase of floating net fishery (FNF) - aquaculture hassome negative impacts on the pollutant loads. In order to preserve the Lake Maninjau ecosystem, continuousmonitoring of water quality is required. This study aims to determine the water quality status andtrophicclassification of Lake Maninjau using the STORET method and trophic classification based on the Regulationof The Minister of Environmental Number 28 of 2009. The results show that over the last ten years (2011–2020), the water quality status of Lake Maninjau were increasingly polluted until it was classed as heavilypolluted, especially in areas with FNF activities. Additionally, the trophic classifications of lake maninjauareeuthropic to hypereutrophic at several FNF locations. Information on the water quality status andtrophicclassification is expected to be taken into consideration in making decisions regarding the management of theLake Maninjau ecosystem.ABSTRAK Danau Maninjau sebagai salah satu Danau Prioritas Nasional berfungsi sebagai pembangkit tenagalistrik, pariwisata, perikanan tangkap, dan perikanan budidaya. Peningkatan aktivitas kerambajaring apung (KJA) yang intensif memberikan dampak buruk terhadap beban pencemar di perairandanau. Sebagai upaya untuk melestarikan ekosistem Danau Maninjau, diperlukan pemantauankualitas air yang dilakukan secara kontinu. Penelitian ini bertujuan untuk menentukan status mutuair dan status trofik di perairan Danau Maninjau dengan menggunakan metode STORETdanklasifikasi status trofik berdasarkan Peraturan Menteri Negara Lingkungan Hidup Nomor 28Tahun2009. Dari hasil penelitian kualitas air selama sepuluh tahun terakhir (2011–2020), terlihat bahwastatus mutu air Danau Maninjau semakin tercemar hingga kelas cemar berat khususnya di areadengan aktivitas KJA. Demikian pula untuk status trofik Danau Maninjau yang berada padakondisi eutrofik hingga hipereutrofik pada beberapa lokasi KJA. Informasi status mutu air dan status trofikini diharapkan dapat dijadikan bahan pertimbangan dalam pengambilan keputusanterkaitpengelolaan ekosistem Danau Maninjau.